Exploring anesthesiologist niche in burn management: Putting the tube where it belongs. A case series on difficult airways in burns - Priyanka Bansal; Nidhi Sultania (Asian Journal of Medical Sciences, 2024)
Burn injuries are complex and challenging, requiring a multidisciplinary approach. We have done more than 15 cases of severely distorted airways in patients with burns (photos attached); although the basic case management remains the same, there are a plethora of other concerns that make these patients unique. The most unique and severe 11 cases we have discussed assiduously. Out of all the concerns, airway management remains the most challenging one. Timely intervention and keen vigilance are required to prevent a disaster later on.